Media Pembelajaran Berbasis Motion Graphic Sebagai Alternatif Materi Mesin Esec 3088 Untuk Teknik Manufaktur Elektronika Politeknik Negeri Batam - Pragus Ilham Nayomi; Arta Uly Siahaan (Politeknik Negeri Batam, 2021)
The motion graphics that are made are about the ESEC 3088 machine which is used as a circuit packaging machine or what is commonly called IC Packaging. So far, students and lecturers of Electronic Manufacturing Engineering have only used material from the ESEC 3088 machine in pdf and word form obtained from e-learning. From this problem, the author made a study